Scheme Implementation as an Effort to Build Originality in Writing - Maryam, Siti (EDUCARE, 2015)
ABSTRACT: Both on the objective and subjective writing, charts/schemes can be used as a means for the (potential) authors to deliver originality. Loading sources and a list of questions on the data chart useful to preserve the objectivity in scientific writing. Materials contained in the scheme need to be processed and lexicalized through varied language. With its potential, if a person continues to practice, he/she will gain the skills , such as writing. Humans can create meanings in the new contexts and situations that can bring something new that commonly called originality. This study was motivated by the importance of originality in writing. Originality is the crown of the creative process; and as a creative product, writing requires creative process. How to build originality in objective and subjective nature of writing? Both of scientific work as an objective writing and writing essays as subjective writing require specific strategies to maintain its originality. The strategies are implemented in different way, because of the natural difference of those writings. The finding of the strategies are based on the results of experimental study carried out on students of Indonesian Language and Literature Department, Faculty of Education and Teacher Training UNSUR (University of Suryakancana) in Cianjur, West Java, Indonesia in different time. This study is expected to provide reference to the author, the writing training instructors, teachers, and lecturers, who develop writing skills. KEY WORDS: Academic writing, essay, originality, objective and subjective writing, schemes, create meanings, creative process, creative product, and develop writing skills.About the Author: Dr. Siti Maryam is a Senior Lecturer at the Faculty of Education and Teacher Training UNSUR (University of Suryakancana) Cianjur, Jalan Dr. Muwardi, Komp Pasirgede Raya, Belakang RS Sayang, Cianjur, West Java, Indonesia. E-mail: yams1964@yahoo.comHow to cite this article? Maryam, Siti. (2015). âScheme Implementation as an Effort to Build Originality in Writingâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.11-22. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (July 6, 2015); Revised (August 6, 2015); and Published (August 25, 2015).